Garton Ash, T. (2023). Tras las huellas de Europa: un relato personal e histórico. Editorial Taurus, 496 pp. - Neves, Hugo (Relaciones Internacionales, 2025)
Reseña de: Garton Ash, T. (2023). Tras las huellas de Europa: un relato personal e histórico. Editorial Taurus, 496 pp.